已知p假q真,则下列公式中为真的是:
A: (p∨[img=12x14]180372e26af2f0b.png[/img]q)∨[img=12x14]180372e27b83e11.png[/img]q
B: (p∨q)∧p
C: p∨[img=12x14]180372e2841ad84.png[/img]q→p
D: [img=12x14]180372e28ca4d4d.png[/img](q∧p)→p
A: (p∨[img=12x14]180372e26af2f0b.png[/img]q)∨[img=12x14]180372e27b83e11.png[/img]q
B: (p∨q)∧p
C: p∨[img=12x14]180372e2841ad84.png[/img]q→p
D: [img=12x14]180372e28ca4d4d.png[/img](q∧p)→p
举一反三
- “只要p,就q”用命题逻辑公式表示是: A: p→q B: q→p C: p«q D: [img=12x14]180372e235da618.png[/img]p∨[img=12x14]180372e23e6984e.png[/img]q
- 下列( )是谓词公式。 A: P(x) B: [img=12x14]180324c8744588e.png[/img]P(x) C: P(x)[img=18x11]180324c87c59fe1.png[/img]Q(x) D: P(x)+Q(x)[img=18x11]180324c884649c1.png[/img]R(x)
- 下列( )是谓词公式。 A: P(x) B: [img=12x14]18038f1536a9c9f.png[/img]P(x) C: P(x)[img=18x11]18038f153e625c4.png[/img]Q(x) D: P(x)+Q(x)[img=18x11]18038f1547a3842.png[/img]R(x)
- 下列( )是谓词公式。 A: P(x) B: [img=12x14]1803673463cbef1.png[/img]P(x) C: P(x)[img=18x11]180367346c00b6c.png[/img]Q(x) D: P(x)+Q(x)[img=18x11]1803673473df1df.png[/img]R(x)
- 下列( )是谓词公式。 A: P(x) B: [img=12x14]18037cdbb50aa38.png[/img]P(x) C: P(x)[img=18x11]18037cdbbe304ab.png[/img]Q(x) D: P(x)+Q(x)[img=18x11]18037cdbc73ccd3.png[/img]R(x)